Handbook of qualitive research - Denzin, Norman K.; Lincoln, Yvonna S. (London Sage Publications, 2000)
The SAGE Handbook of Qualitative Research, Third Edition, represents the state of art for the theory and practice of qualitative inquiry. Built on the foundations of the landmark First and Second Editions (1994, 2000), the Third Edition moves qualitative research boldly into the 21st century. The editors and authors ask how the practices of qualitative inquiry can be used to address issues of social justice in this new century.